PIWI pathway against viruses in insects. (10th June 2019) - Kolliopoulou, Anna; Santos, Dulce; Taning, Clauvis Nji Tizi; Wynant, Niels; Vanden Broeck, Jozef; Smagghe, Guy; Swevers, Luc
Abstract: Piwi‐interacting RNAs (piRNAs) are an animal‐specific class of small non‐coding RNAs that are generated via a biogenesis pathway distinct from small interfering RNAs (siRNAs) and microRNAs (miRNAs). There are variations in piRNA biogenesis that depend on several factors, such as the cell type (germline or soma), the organism, and the purpose for which they are being produced, such as transposon‐targeting, viral‐targeting, or gene‐derived piRNAs. Interestingly, the genes involved in the PIWI/piRNA pathway are more rapidly evolving compared with other RNA interference (RNAi) genes. In this review, the role of the piRNA pathway in the antiviral response is reviewed based on recent findings in insect models such as Drosophila, mosquitoes, midges and the silkworm, Bombyx mori . We extensively discuss the special features that characterize host‐virus piRNA responses with respect to the proteins and the genes involved, the viral piRNAs' sequence characteristics, the target strand orientation biases as well as the viral piRNA target hotspots across the viral genomes. This article is categorized under: Regulatory RNAs/RNAi/Riboswitches > RNAi: Mechanisms of Action Regulatory RNAs/RNAi/Riboswitches > Biogenesis of Effector Small RNAs Abstract : A detailed comparison between three insect models (Drosophila melanogaster, Bombyx mori, Aedes aegypti) is made in this review with regard to the response of PIWI pathway against viral infections.